Analisis SWOT Integrasi Data OSS dan SIINas Menggunakan Single Sign-On untuk Meningkatkan Efektivitas Pengelolaan Industri di Jawa Timur - Vemas Catur Kurniawan; Minto Waluyo (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Optimizing industrial management is key to spurring economic growth in East Java, particularly through the optimization of digital platforms, namely the Online Single Submission (OSS) and the National Industrial Information System (SIINas). Unfortunately, the operation of these two platforms is not yet integrated, resulting in complex administrative flows, data duplication, and lack of easy access, especially for small and medium enterprises (SMEs) that are not yet familiar with technology, which are common challenges. Many business owners experience difficulties in understanding and using digital systems, so they need simpler and more accessible solutions. This study aims to analyze the need for implementing a Single Sign-On (SSO) system as a solution to integrate data between OSS and SIINas to improve efficiency, transparency, and ease of use. The results show that implementing SSO can help reduce administrative burdens, increase transparency, and speed up processes. However, several challenges remain, such as the community's inability to accept technology, limited technological infrastructure, and the need for digital training for business owners who are not yet familiar with it. Recommended strategies include strengthening technological infrastructure, providing easy-to-understand training, providing offline access, and strengthening data security systems.